Bez bolu, bez tabletek : wielka ksiega akupresury - Bernau, Lutz.; Meyer, Adolf-Ernst. (Warszawa : W.A.B., 1997)
Polish translation of "Schmerzfrei ohne Tabletten durch Akupressur". The author offers answers all questions about the usefulness of acupressure after many years of study in China.
Keywords: Acupressure; Pain